Overestimation of microbial community respiration caused by nitrification, and the identification of keystone groups associated with respiration - Zhang, Lianbao; Zhou, Wei; Wang, Yanwei; Liu, Yeping; Chen, Junfeng; Li, Bin; Su, Bei; Song, Hui (Frontiers in Marine Science, 2024)
Microbial community respiration (MCR) strongly controls the fate of organic carbon in the ocean. The balance between MCR and primary production strongly determines whether the ocean is a net sink or source of CO2 to the atmosphere. Thus, it is necessary to estimate MCR to better understand the role of oceans in the global carbon cycle. Methods based on apparent oxygen utilization (AOU) are predominant while electron transport system (ETS) assay gets increasing attention. Although methods get developed, few studies on MCR have been performed on a seasonal cycle. Because MCR is strongly associated with the temperature which changes along with the succession of seasons, it is urgent to study the MCR on a seasonal cycle. Thus, we measured the MCR based on AOU and ETS methods simultaneously from